2016
DOI: 10.1002/14651858.cd010735.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted cataract surgery versus standard ultrasound phacoemulsification cataract surgery

Abstract: Laser-assisted cataract surgery versus standard ultrasound phacoemulsification cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 48 publications
3
108
0
6
Order By: Relevance
“…In our patients we found similar surgical outcomes to those published with traditional manual cataract surgery regarding IOP, VA, and VF, with the added advantage of femtosecond laser precision. 13 Suction was well tolerated in glaucomatous eyes during surgery, showing no signi cant mean IOP raise immediately after suction docking or up to our 90-day nal follow-up. This contrasts with previous studies of FLACS performed in glaucomatous eyes.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In our patients we found similar surgical outcomes to those published with traditional manual cataract surgery regarding IOP, VA, and VF, with the added advantage of femtosecond laser precision. 13 Suction was well tolerated in glaucomatous eyes during surgery, showing no signi cant mean IOP raise immediately after suction docking or up to our 90-day nal follow-up. This contrasts with previous studies of FLACS performed in glaucomatous eyes.…”
Section: Discussionmentioning
confidence: 70%
“…11,12 The superiority of FLACS compared to manual phacoemulsi cation cannot be determined with the evidence available today. 13 Considering the characteristics of glaucoma patients, and the added risk of IOP rising during the docking procedure in eyes with an additional vulnerability to IOP changes, we nd it is important to assess the outcomes of FLACS in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The cataract surgery pharmacological support in glaucoma patients (including 0.5 % levofloxacin, 0.09 % bromfenac and preservative free polyvinylpyrrolidone and polyvinyl alcohol fixed combination instillations) showed: high efficiency (in prevention of infectious and inflammatory complications); safety by influence on the ocular surface; comfort of use. Keywords: cataract surgery, glaucoma, pharmacological support, ocular surface, 0.09 % bromfenac For citation: Катарактальная хирургия, включая ультразвуковую факоэмульсификацию (ФЭК) и фемтолазер-ассистированную ФЭК, является высокоэффективным и безопасным вмешательством [1,2]. Вместе с тем в послеоперационном периоде у части пациентов возможно появление или отягощение клинических проявлений синдрома «сухого глаза» (ССГ), снижающих удовлетворенность результатами лечебного воздействия [3][4][5][6][7].…”
Section: Discussionunclassified
“…Effectiveness and Safety of Cataract Surgery Pharmacological Support in Glaucoma Patients S.V. Yanchenko 1,2 , A.V. Malyshev 1,2 , S.N.…”
mentioning
confidence: 99%
“…A meta-analysis study concluded that FLACS was not superior to conventional phacoemulsification surgery in terms of intraoperative and postoperative complications [102]. A Cochrane systematic review including 16 randomized clinical trials that compared FLACS with conventional phacoemulsification surgery also failed to determine the superiority of FLACS [103]. erefore, further development of FLACS would be needed to provide significant improvement in safety and efficacy and to reduce costs to keep health systems sustainable.…”
Section: Limitations and Complicationsmentioning
confidence: 99%